Intra- and Inter-observer Variability of Computed Tomographic Measurements of the Prostate Gland in Neutered Dogs - Delaude, Alessandro; Broeckx, Bart J. G.; Saunders, Jimmy H.; De Winter, Lauren; Hillaert, Amber; Stock, Emmelie (Frontiers in Veterinary Science, 2021)
The purpose of this study was to evaluate the intra- and interobserver variability of computed tomographic measurements of linear prostate dimensions in neutered dogs without signs of prostatic disease, to determine potential associations between prostatic parameters and body weight or age and to provide reference ranges. Length, width and height of the prostate gland were measured in 62 neutered dogs with no signs of prostatic disease by three observers with different levels of training. Statistically significant positive associations were found between all prostatic parameters and body weight, but not with age. Formulae allowing the calculation of the expected values for prostatic parameters based on body weight are provided (length = 15.3 + body weight (BW) x 0.3; height = 9.7 + BW x 0.16; width = 9.5 + BW x 0.2). These may represent a useful tool for computed tomographic evaluation of the size of the prostate in neutered dogs. Subjective evaluations of the morphological appearance of the prostate gland are also provided.